2020
DOI: 10.1111/1742-6723.13545
|View full text |Cite
|
Sign up to set email alerts
|

Oxycodone prescribing in the emergency department during the opioid crisis

Abstract: There is a higher incidence of oxycodone prescribing in the Australian ED than previously recognised. An overuse of oxycodone may be contributing to adverse patient outcomes and a public health crisis. Hospitals should consider appropriate steps to reduce the incidence of opioid prescribing and the supply of these medications into the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Elements of opioid prescribing associated with an increased risk of complications include excessive initial days’ supply, high doses, concurrent prescribing of opioids and sedatives, and long-term prescribing [ 8 – 11 ]. Hospital-initiated opioids, most often for acute pain management, have been identified as a key risk for ongoing and inappropriate use [ 8 , 9 ]. Accumulating observational evidence suggests that therapeutic exposure to opioids is associated with increased likelihood of long-term use and that greater duration or intensity of initial opioid prescriptions may further elevate risk [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elements of opioid prescribing associated with an increased risk of complications include excessive initial days’ supply, high doses, concurrent prescribing of opioids and sedatives, and long-term prescribing [ 8 – 11 ]. Hospital-initiated opioids, most often for acute pain management, have been identified as a key risk for ongoing and inappropriate use [ 8 , 9 ]. Accumulating observational evidence suggests that therapeutic exposure to opioids is associated with increased likelihood of long-term use and that greater duration or intensity of initial opioid prescriptions may further elevate risk [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in Australia, using group-based trajectory modelling to define persistent use, found that 2.6% of adults initiating opioids became persistent users over a 12-month period [ 16 ]. Further research suggests concerns regarding the appropriateness and number of opioid prescriptions written on discharge [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The opioid epidemic represents the advent of signi cant public health challenges, setting the stage for substantial public health cost (Seaton et al, 2007;Pouryahya et al, 2020). The most readily prescribed and abused opioids include buprenorphine, morphine, and oxycodone (OXY), each often prescribed to women as an analgesic for postpartum treatment (Hodder et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The most readily prescribed and abused opioids include buprenorphine, morphine, and oxycodone (OXY), each often prescribed to women as an analgesic for postpartum treatment (Hodder et al, 2021). OXY is teratogenic and readily crosses the placental barrier leading to impairments in fetal development (Pouryahya et al, 2020). Several of our previously published studies have provided evidence of phenotypic, behavioral, biochemical, and synaptic vulnerabilities of postnatal OXY-exposed offspring (PNO) and in utero OXYexposed offspring (IUO) in early life and adulthood (Doberczak et al, 1991;Jones et al, 2010;Shahjin et al, 2019;Odegaard et al, 2020a;Odegaard et al, 2020b;Odegaard et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Opioids accounted for 23.2% of ED discharge prescriptions 3 and were provided on discharge for 6.4% of patient presentations. 4 Opioid prescribing requires careful planning due to potentially serious adverse outcomes, including dependence and overdose. [5][6][7][8] To reduce this risk, opioids should be used at the lowest effective dose for the shortest appropriate duration.…”
Section: Introductionmentioning
confidence: 99%